2014
DOI: 10.5114/pwki.2014.41475
|View full text |Cite
|
Sign up to set email alerts
|

Acute inferior myocardial infarction in a patient with a prosthetic aortic valve and high international normalized ratio

Abstract: ST elevation acute myocardial infarction in patients with a mechanical prosthetic valve is rare and usually due to inadequate anticoagulation. We present a case of acute inferior myocardial infarction in a patient with a prosthetic aortic valve and high international normalized ratio, which has not been reported previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…But after a course of anticoagulation therapy for about three months, we found that the thrombi were eliminated completely. Although most myocardial infarction in patient taking oral anticoagulation is due to inadequate anticoagulation, it is also possible that myocardial infarction may occur despite normal therapeutic range of INR (8). There is no consensus in the treatment of coronary embolism due to prosthetic valve thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…But after a course of anticoagulation therapy for about three months, we found that the thrombi were eliminated completely. Although most myocardial infarction in patient taking oral anticoagulation is due to inadequate anticoagulation, it is also possible that myocardial infarction may occur despite normal therapeutic range of INR (8). There is no consensus in the treatment of coronary embolism due to prosthetic valve thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, uninterrupted OAC with VKA may offer an economic benefit related to shorter hospitalization. Based on the above-presented results in patients with therapeutic INR 2–3.0 during PCI dual antiplatelet therapy, no additional heparin bolus and radial access seem the first choice strategy [10, 13]. An additional UFH bolus or bivalirudin (especially at high risk of bleeding) may be considered in patients with INR < 2.0, complex lesion PCI or prolonged procedure; however, glycoprotein IIb/IIIa inhibitors should be avoided (Figure 1).…”
Section: Peri-procedural Antithrombotic Managementmentioning
confidence: 99%